Coping with the worst of both worlds: phenotypic adjustments for cold acclimatization benefit northward migration and arrival in the cold in an Arctic breeding songbird ... - Le Pogam, Audrey; O'Connor, Ryan S.; Love, Oliver P.; Petit, Magali; Régimbald, Lyette; Vézina, François (Dryad, 2021)
Cold acclimatization (phenotypic adjustments to cope with cold conditions) is an imperative requirement for birds living at high latitudes during the cold depths of winter. Despite the significant remodelling of key phenotypic traits and energetic costs associated with elevating cold endurance, winter cold acclimatization can also provide further carryover benefits to subsequent stages in species wintering, migrating and breeding in cold environments (e.g., the Arctic). We tested this beneficial carryover hypothesis using outdoor captive Arctic-breeding snow buntings (Plectrophenax nivalis), a cold specialist known for its impressive wintering thermogenic capabilities. We compared changes in phenotypic traits supporting cold acclimatization – body composition (body, fat, lean mass, pectoral muscle thickness), oxygen carrying capacity (hematocrit), thermogenic capacity and endurance (Msum, time to Msum), cold tolerance (Ta at Msum) and maintenance energy expenditure (BMR) – between the wintering, migratory ...